Selected Ratio and Bankruptcy Early-Warning Method Analysis of Competitiveness of Wood Sector Companies Listed on Warsaw Stock Exchange - Justyna Biernacka (University of Zagreb, Faculty of Forestry and Wood Technology, 2012)
This paper presents the analysis of economic conditions of wood sector companies listed on the Warsaw Stock Exchange. Among many measures of ratio analysis, the three most frequently used groups of indicators - profitability, debt and liquidity were selected. For a comprehensive presentation of the situation of each company, the Mączyńska & Zawadzki’s model was used as the bankruptcy early warning method. Two furniture industry companies, two wood-based panel industry companies, two pulp and paper industry entities, a representative of sawmilling industry and a company of wood-based panels and furniture industry were analyzed. The analysis showed that companies with stabile position in the market have the best economic conditions, and these were namely the pulp and paper industry and furniture industry.